Investment liberalization and facilitation toward AEC 2015 - Aldaba, Rafaelita M. (Philippine Journal of Development, 2012)
The paper examines the state of investment liberalization and facilitation in the Philippines and suggests policy measures to enable the country to comply with its ASEAN Economic Community (AEC) 2015 commitments. Based on interviews and surveys, the results indicated that investment incentives, low tax rates, and time/cost of starting a business are critical factors affecting firms` decision to invest in the Philippines. The respondents noted significant improvements in political stability and level of corruption. A great majority of the firms also indicated future expansion of their operations and the ASEAN market as significant factors in their investment decisions.